Interface Methods of Teaching Modern Foreign Languages in Universities and Institutions - Taryanikova Marina Anatolyevna (Genius Journals, 2022)
The content of the article Modern methods of teaching English in higher educational institutions is in scientifically based opinions on improving the effectiveness of the educational process based on interactive ideas. At the same time, one of the main goals is to provide students with the necessary conditions in the process of teaching, to show them on a scientific basis that they will become more knowledgeable, capable and mature professionals. By analyzing the shortcomings that arise today due to lack of knowledge and skills, we can further increase the interest of students by localizing their modern experience, using the opportunities in our country.
Keywords: Higher educational institutions; modern teaching methods; interactive ideas; efficiency